Problem of Competition and Support in Economy, its Practical Aspects - Matiušaitytė, Raimundė; Jasinskas, Edmundas (Ekonomika, 2004)
The government plays a pervasive role in the economy. It has a variety of roles: it sets the legal framework within witch all households and firms take actions; government acts as a producer and consumer. Government plays its indirect roles in affecting bow households and firms behave too. It regulates and subsidizes.In this article is analysed importance of competition for economical development, different opinions of mercantilists, classical economical theory, Keynesian theory, and neoclassical theory about competition and support for business sector. There are analysed principles or EU competition policy, its influence to business sector and markets. Especially emphasised are problems of competition and support in agriculture sector.The aim of the study is to analyse points of view of different theories about government’s policy of competition and support, EU policy of competition, problems of competition and support in agriculture. The object of study: policy of competition and support. The following methods are used in the study: the analysis and the synthesis of the scientific literature, abstraction, interview and qualitative analysis of the obtained data.The main conclusions of the work: there still persist different opinions about government’s interfering in free economy, competition and subsidizing. Ground of EU economical order is principle of free competition, but it is combined with support. There are most problems in agriculture sector because of relative big support for firms in this area. Support for agriculture sector in Lithuania will change preferences and specialisation of firms acting in this sector.